1999
DOI: 10.4141/s98-061
|View full text |Cite
|
Sign up to set email alerts
|

Protected organic matter in water-stable aggregates as affected by mineral fertilizer and manure applications

Abstract: N. 1999. Protected organic matter in water-stable aggregates as affected by mineral fertilizer and manure applications. Can. J. Soil Sci. 79: 419-425. Effects of long-term (18-yr) applications of cattle manure (20 Mg ha -1 yr -1 ) and NPK fertilizer on the labile organic matter (OM) and its protection in water-stable aggregates were investigated in a Le Bras silt loam (Humic Gleysol). Soil from the 0-to 10-cm depth was sampled from the untreated control, NPK, manure and NPK + manure treatments and fractionated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 20 publications
7
42
0
1
Order By: Relevance
“…Aggregate water stability and soil aggregation are known to play a major role in improving soil fertility and grain production. The application of manure increases the percentage of large sized water stable aggregates (> 5 mm) (Aoyama et al 1999). Similar results were found in this study.…”
Section: Resultssupporting
confidence: 81%
“…Aggregate water stability and soil aggregation are known to play a major role in improving soil fertility and grain production. The application of manure increases the percentage of large sized water stable aggregates (> 5 mm) (Aoyama et al 1999). Similar results were found in this study.…”
Section: Resultssupporting
confidence: 81%
“…Studies have shown that manure application increased SOC and nutrient status in the soil (Webster and Goulding, 1989;Collins et al, 1992;Rochett e and Gregorich, 1998) and labile carbon pools (Aoyama et al, 1999;Mikha and Rice, 2004). Total corn rootderived C (C in root biomass plus that in rhizodeposition) contributes from 1.5 times to more than 3 times more C to SOC than shoot-derived C (Balesdent and Balabane, 1996;Wanniarachchi et al, 1999;Wilts et al, 2004;Hooker et al, 2005).…”
Section: Biomass and Bioenergy Concernsmentioning
confidence: 99%
“…Disaggregation occurred in all treatments after 20 days of incubation due to probably the more substrate demands of microorganisms in soil (Gulser, 2010). The application of manure and organic fertilizer increases the percentage of large sized water stable aggregates (> 5mm) (Aoyama et al, 1999 andWang et al, 2013). Usually, there was a significant positive correlation between mean weight diameter (MWD) and the amount of > 0.25mm aggregates (Guber et al, 2005).Most of organic fertilizer treatments had large MWD and high amount of > 0.25mm aggregates (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%